Transactions on Engineering Technologies Special Volume of the World Congress on Engineering 2013 - Yang, Gi-Chul; Ao, Sio-Iong; Gelman, Len (Springer Netherlands : Imprint: Springer, 2014)
This book contains revised and extended research articles written by prominent researchers participating in the international conference on Advances in Engineering Technologies and Physical Science (London, U.K., 3-5 July, 2013).  Topics covered include mechanical engineering, bioengineering, internet engineering, image engineering, wireless networks, knowledge engineering, manufacturing engineering, and industrial applications. The book offers state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science.